Detection and molecular characterization of a highly oncogenic Marek's disease virus from vaccinated hens in Turkey - Abayli, Hasan; Karabulut, Burak; Ozbek, Remziye; Ongor, Hasan; Timurkaan, Necati; Tonbak, Sukru (Frontiers Media Sa, 2021)
Marek's disease (MD) is a highly contagious neoplastic disease of chickens associated with economic losses, often due to visceral lymphomas. The etiological agent is MD virus serotype 1 (MDV-1), also called Gallid alphaherpesvirus 2 (GaHV-2). Despite intensive vaccination, MDV is constantly evolving and maintaining its presence in the world. The aim of this study was to genetically analyze a highly oncogenic MDV/Tur/2019 strain obtained from a poultry farm in Turkey's Elazig province in 2019. Genes associated with viral pathogenicity and oncogenicity Marek's EcoRI-Q-encoded protein (MEQ), phosphoprotein-38 (pp38), and viral interleukin 8 (vIL-8) were selected for this purpose. The vIL-8 nucleotide sequence showed high similarity (100% identity) to some European (EU-1, Polen 5) and Asian (03 India, GADVASU-M2) MDV strains. The pp38 nucleotide sequence showed high similarity (100% identity) to some American (CU-2, JM/102W, RB1B) and European (MD70/13, ATE2539) MDV strains. There were no disrupted four-proline molecules (PPPP) within the transactivation domain of the MEQ. However, according to phylogenetic results, the MDV/Tur/2019 strain was included in cluster 2a alongside European MDV strains (Polish, Hungarian, Italian) with very virulent and very virulent plus pathotypes. In conclusion, we believe that the MDV/Tur/2019 strain obtained from turkey herpesvirus (HVT)-vaccinated chickens has a very virulent or very virulent plus pathotype. Although this result provides some clues regarding the virulence of this strain, in vivo studies are needed to achieve exact pathotyping. Further, combination of HVT with the CVI988 strain should be used for vaccination to provide the best protection, as highly pathogenic MDV strains can break sterile immunity against the HVT vaccine.
Keywords: GaHV-2; Marek's disease; oncogenes; Turkey